2017
DOI: 10.1200/jco.2017.35.15_suppl.e23075
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of anti-PD-1/PD-L1 antibodies for treatment of advanced or refractory cancers: A meta-analysis.

Abstract: Purpose: To systematically evaluate the overall efficacy and safety of current anti-PD-1/PD-L1 antibodies for treatment of patients with advanced or refractory cancer.Results: Fifty-one trials including 6,800 patients were included. The overall response rates for melanoma, non-small cell lung cancer (NSCLC), and renal cell carcinoma (RCC) were 29% (95% CI: 1.53−2.41), 21% (95% CI: 17%−25%) and 21% (95% CI: 16%−27%) respectively. While the overall adverse effects rate for melanoma, NSCLC, RCC were 16% (95% CI: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…28 The incidence of TRAEs associated with ICIs ranged from 9% to 31%, with a pooled rate of 16% (95% confidence interval, 12%-21%). 30 Treatment with ICIs was associated with a higher incidence of any-grade and grade 3 to 4 irAEs (ie, rash, aspartate aminotransferase increase, hypothyroidism, colitis, and pneumonitis) compared with non-ICI regimens. 31 The incidence of IRRs and hypersensitivity reactions occurring with avelumab and other ICIs was similar to or less than the incidence reported with other systemic and targeted treatments, including commonly used taxane-based chemotherapy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…28 The incidence of TRAEs associated with ICIs ranged from 9% to 31%, with a pooled rate of 16% (95% confidence interval, 12%-21%). 30 Treatment with ICIs was associated with a higher incidence of any-grade and grade 3 to 4 irAEs (ie, rash, aspartate aminotransferase increase, hypothyroidism, colitis, and pneumonitis) compared with non-ICI regimens. 31 The incidence of IRRs and hypersensitivity reactions occurring with avelumab and other ICIs was similar to or less than the incidence reported with other systemic and targeted treatments, including commonly used taxane-based chemotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…Meta-analyses of the safety and tolerability of anti-PD-L1/PD-1 agents corroborate findings of improved safety profiles of ICIs compared with chemotherapy regimens used to treat patients with advanced cancers. [28][29][30][31] In a meta-analysis of 3450 patients from 7 randomized controlled trials, treatment with ICIs was associated with a lower incidence of any-grade AEs compared with chemotherapy (67.6% vs 82.9%) and grade 3 to 4 AEs (11.4% vs 35.7%), and treatment discontinuation occurred less frequently with anti-PD-L1/PD-1 agents compared with chemotherapy (4.5% vs 11.1%). 28 The incidence of TRAEs associated with ICIs ranged from 9% to 31%, with a pooled rate of 16% (95% confidence interval, 12%-21%).…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38] Some concluded that combination immunotherapy could result in better antitumor efficacy, but were based on only one or two studies. 31,38 One network meta-analysis compared ICIs with targeted therapies for metastatic melanoma, suggesting that a combination of BRAF and MEK inhibitors was superior to anti-CTLA-4 agents and anti-PD-1 agents. As far as we know, no other meta-analysis assessed the added benefits against the toxicity of each drug in the combination.…”
Section: Agreement/disagreement With Previous Meta-analysesmentioning
confidence: 99%
“…We built upon the ordinary differential equation model explored in the original sycnhrionized lysis circuit system (19). The following set of ordinary differential equations were derived to describe the bacterial population number (N, equation [1]), total extracellular AHL (H, equation [2]), intracellular concentrations of the lysis protein E (L, equation [3]), intracellular concentrations of the LuxI protein (I, equation [4]), and intracellular concentrations of the PD-L1 Nb protein (P, equation [5]). In this system, bacteria grow logistically at a rate of µ N to a maximum capacity, N 0 and lyse once at quorum.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…These inhibitory checkpoint blockade mechanisms have prompted the exploration of blocking monoclonal antibodies (mAbs) as therapeutics against these molecules. While anti-PD-L1 mAbs have achieved some level of tumor regression in ~30% of cancers like melanoma (4,5), they can also result in immune-related adverse effects (iRAEs), with up to 70% of patients experiencing a range of toxicity grades resulting in fatigue, skin rashes, endocrine disorders, or hepatic toxicities (6)(7)(8)(9). Furthermore, combination therapies of anti-PD-L1/PD-1 mAbs and anti-cytotoxic T-lymphocyte associated protein-4 (CTLA-4) mAbs are more efficacious than monotherapies, but cause higher grade toxicities that lead to favoring of less efficacious monotherapies or eventual drug discontinuation (10,11).…”
Section: Introductionmentioning
confidence: 99%